Six‐year population dynamics of seven passalid species in a humid tropical rainforest in Borneo. Issue 4 (6th October 2021) - Ueno, Hiroto; Araya, Kunio; Meleng, Paulus; Kaliang, Clement Het; Sakai, Shoko; Kishimoto‐Yamada, Keiko; Kon, Masahiro; Itioka, Takao; Satake, Akiko
Abstract: Phenology of insect abundance in less seasonal tropical regions is well recognized. Even in Bornean tropical forests in Malaysia, where there is no distinct dry season, there are insect species that behave as if their environments were highly seasonal. How such seasonal dynamics are shaped and what factors determine the seasonality remains largely unresolved. To elucidate the mechanisms underlying population dynamics in relatively stable tropical environments, we classified monthly samples collected with light traps at Lambir Hills National Park, Malaysia, and generated long‐term time‐series data for the family Passalidae (Coleoptera: Scarabaeoidea), which spend nearly their entire life cycle within or beneath decayed wood. Analyses of our data (20 species and 768 individuals) revealed that there were clear abundance peaks in April and October at the community level. We analyzed the data together with climate data using a nonlinear time‐series analysis called convergent cross mapping. The causal relationship between adult population dynamics of the dominant species ( Leptaulax planus ) and temperature was detected, which shows that the population dynamics of L. planus are driven by cool temperatures approximately 1 month before emergence. Our study indicates that even in perpetually wet tropical rainforests in Southeast Asia, insect population dynamics respond to climatic factors and show seasonal population dynamics. Abstract : We provided high‐quality time‐series data on the abundance of saproxylic insects collected by monthly light‐trapping from 1993 to 1999 in a Bornean tropical rainforest. Our data is the first showing clear seasonality in the community dynamics of saproxylic insects with clear abundance peaks in April and October. We found that the seasonal dynamics of most abundant species were driven by cool temperatures approximately 1 month before emergence.